Effect of the Quality of Accounting Information on the Efficiency of Investment Decisions - يحيى, عباس حميد; ثابت, علي ناصر (Journal of Economics and Administrative Sciences, 2017)
AbstractThe entities responsible for regulating the financial market are seeking to provide high quality accounting information, to provide appropriate protection to investors, and thus encourage them and attract them to increase their investments. the research reached several conclusion, the most prominent of which comes  :-1-The production of high quality accounting information reduces investment costs and costs of processing accounting information.2- The production of high quality accounting information helps investors identify the best investment opportunities.3- The results of the statistical analysis showed that there is significant relationship between the quality of accounting information and efficiency investment decision in the sample banks.The research also reached several recommendations, most notably the following :-1-Necessity to oblige all companies to reduce high quality accounting information to provide reasonable protection for investors.2-Necessity to oblige all companies to reduce high quality accounting information to increase the efficiency of investment, thus attracting capital and foreign investment.